2020
DOI: 10.1002/term.3077
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase suppresses the inflammatory response in anterior cruciate ligament fibroblasts and promotes tissue regeneration by targeting myotrophin via the nuclear factor‐kappa B pathway

Abstract: Anterior cruciate ligament (ACL) regeneration is severely affected by the injury‐induced overexpression of matrix metalloproteinases (MMPs) and downregulation of lysyl oxidase (LOX). Previous studies have focused on how the expression of MMPs and downregulation of LOX are physiologically balanced at injured sites for regenerating the ACL tissue, but the role of LOX in regulating cellular functions has not been investigated yet. Herein, we conducted an in vitro cellular experiment and unexpectedly found that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In animal experiments, TNC induced the recruitment of STSCs to the injured area, significantly accelerating the early repair of tendon tissue, clearly apparent from the accumulation of type I collagen and the restoration of the structure of the tissue. 22 However, excessive secretion of type I collagen in the late stages of tissue repair is not appropriate for the functional regeneration of tendon tissue. Excessive fibrosis caused by type I collagen would cause a repaired tendon to have poor mechanical strength, resulting in failure of the regenerated tendon.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, TNC induced the recruitment of STSCs to the injured area, significantly accelerating the early repair of tendon tissue, clearly apparent from the accumulation of type I collagen and the restoration of the structure of the tissue. 22 However, excessive secretion of type I collagen in the late stages of tissue repair is not appropriate for the functional regeneration of tendon tissue. Excessive fibrosis caused by type I collagen would cause a repaired tendon to have poor mechanical strength, resulting in failure of the regenerated tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid metabolism is thought to be involved in the pathogenesis of OA ( Li et al, 2016b ), and a variety of amino acids are abnormally expressed in OA chondrocytes ( Mickiewicz et al, 2015 ; Zheng et al, 2017 ). Unlike most tissues, articular cartilage has no blood vessels, nerves, or lymphatic vessels and is composed mainly of extracellular matrix (ECM) and chondrocytes ( Wang et al, 2020b ). ECM mainly consists of water, collagen, and proteoglycans ( Sophia Fox et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the primary energy source of chondrocytes is glycolysis ( Lane et al, 2015 ), and disorders of glycolytic metabolism can lead to chondrocyte hypertrophy and extracellular matrix degradation, promoting OA development ( Kudelko et al, 2016 ). Generally, in healthy joints, chondrocytes are in metabolic balance ( Wang et al, 2020b ). In OA joints or inflammatory environments, chondrocytes undergo metabolic reprogramming, enhancing the glycolytic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous research, it has been proposed that the pathogenesis of osteoarthritis is connected with the deformation of joints which occurs because of the vitiated cartilage. Although, multiple studies with deep research also demonstrate the crucial character of inflammatory reaction in the pathogenesis of osteoarthritis [6,7]. TNF-α is the main inflammatory element of cartilage deformation in osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%